Hemodynamic and oxidative stress effects of gamma-radiation in both male and female rats - Maulood, Ismail M.; Ahmed, Ali H.; Othman, Hawzeen K. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Objective.The present study aimed to determine the alteration in hemodynamic and oxidative stress caused by gamma-irradiation in both sexes of rats. Materials and Methods: Twenty-four albino rats were randomly divided into two groups The first group includes twelve rats (Six males and six females) served as control, while the rats of the second group (six males and six females) were exposed to gamma radiation through 0.763 Gy from Cesium-137 radioactive source for two weeks. Results: Gamma radiation exposure significantly raised malondialdehyde (MDA) levels. Furthermore, serum AST activity was greatly altered by gamma-radiation, while the ALT activity significantly increased by the gamma radiation in female rats only. Irradiated animals caused signification in blood pressure. Gamma-irradiation animals for both sexes resulted in significant decrease in serum calcium (Ca+2) levels in both male and female rats. Conclusion, our results demonstrated that gamma- irradiated rats could increase tissue injuries markers and lipid peroxidation productions. Interestingly, the elevated blood pressure by gamma-ray exposure may be returned to high free radicals and changes in calcium ions.
Keywords: Gamma ray; Oxidative stress; Blood pressure; tissue injury markers